The Socio-Demographic Impacts on Islamic Character Education: A Comparative Study of Madrasah Aliyah Students in Urban and Rural Areas - Suci Amellia; Maria Noor; Nadya Ranialini; Pitra Gosha Patriasya; Andelina Damayanti (WISE Pendidikan Indonesia, 2025)
This study examines the socio-demographic impacts on Islamic character education among Madrasah Aliyah students, comparing urban and rural environments in Lampung Province, Indonesia. The aim of this study is to explore how social, economic, and cultural backgrounds influence students' understanding and internalization of religious moderation in character education. Data were collected through direct classroom observations, in-depth interviews with students, teachers, and madrasah principals, as well as document analysis from four selected madrasahs: Madrasah Aliyah Negeri (MAN) 2 Bandar Lampung and MA Al-Utrujiyyah in urban areas, and MAN 1 Pesawaran and MA Darul Huda in rural areas. A qualitative approach with a descriptive phenomenological design was used to analyze the differences in students' understanding of religious moderation between urban and rural areas. The findings show that students in urban areas, with broader access to information and exposure to diverse cultures, exhibit a more inclusive and dynamic understanding of Islamic values such as tolerance and diversity. In contrast, students in rural areas, who are more reliant on traditional teachings and have limited access to external information, tend to have a more rigid understanding of Islamic teachings. These differences highlight the importance of adapting Islamic character education to the socio-demographic context in both urban and rural environments. This study contributes to the development of an inclusive Islamic character education model that supports religious moderation and social harmony across various environments.